Nitride-based laser diodes and superluminescent diodes - Perlin, Piotr; Stańczyk, Szymon; Kafar, Anna; Bojarska, Agata; Marona, Łucja; Czernecki, Robert; Targowski, Grzegorz; Muzioł, Grzegorz; Turski, Henryk; Grzanka, Ewa; Grzanka, Szymon; Wiśniewski, Przemek; et al. (Photonics Letters of Poland, 2014)
We report on the development of nitride laser diode technology leading towards higher optical power, better quality and larger versatility of these devices. In particular we discuss new concepts introduced in Institute of High Pressure Physics “Unipress” such as: new design of the laser diode waveguide by profiting from plasmonic substrate properties of the material, design and fabrication of high optical power laser diode arrays, construction of high power nitride based superluminescent diodes and high-indium content devices grown by molecular beam epitaxy. Full Text: PDF References S. Nagahama, M. Sano, T. Yanamoto, D. Morita, O. Miki, K. Sakamoto, M. Yamamoto, Y. Matsuyama, Y. Kawata, T. Murayama, T. Mukai, "GaN-based laser diodes emitting from ultraviolet to blue-green", Proc. of SPIE 4995, 108-116 (2003). CrossRef M. Sarzyński, M. Kryśko, G. Targowski, R. Czernecki, A. Sarzyńska, A. Libura, W. Krupczyński, P. Perlin, and M. Leszczyński, "Elimination of AlGaN epilayer cracking by spatially patterned AlN mask", Appl. Phys. Lett. 88, 121124 (2006). CrossRef G. A. Smolyakov, P. G. Eliseev, and M. Osinski, "Effects of resonant mode coupling on optical Characteristics of InGaN-GaN-AlGaN lasers", IEEE J. Quantum Electron. 41, 4, 517 (2005). CrossRef P. Perlin, K. Holc, M. Sarzynski, W. Scheibenzuber, L. Marona, R. Czernecki, M. Leszczynski, M. Bockowski, I. Grzegory, S. Porowski, G. Cywinski, P. Firek, J. Szmidt, U. Schwarz, and T. Suski, "Application of a composite plasmonic substrate for the suppression of an electromagnetic mode leakage in InGaN laser diodes", Appl. Phys. Lett. 95, 261108 (2009). CrossRef S. Stańczyk, T. Czyszanowski, A. Kafar, R. Czernecki, G. Targowski, M. Leszczyński, T. Suski, R. Kucharski, and P. Perlin, "InGaN laser diodes with reduced AlGaN cladding thickness fabricated on GaN plasmonic substrate", Appl. Phys. Lett. 102, 151102 (2013). CrossRef N. Ikeda, T. Mizuno, N. Takeya, S. Goto, S. Ikeda, T. Fujimoto, Y. Ohfuji, and T. Hashizu, "High-power GaN-based semiconductor lasers", Phys. Status Solidi C 1 (2004) 1461. CrossRef M. Meneghini, N. Trivellin, K. Orita, S. Takigawa, T. Tanaka, D. Ueda, G. Meneghesso, and E. Zanoni "Degradation of InGaN-based laser diodes analyzed by means of electrical and optical measurements", Appl. Phys. Lett. 97 (2010) 263501. CrossRef P. Perlin, L. Marona, K. Holc, P. Wisniewski, T. Suski, M. Leszczynski, R. Czernecki, S. Najda, M. Zajac, and R. Kucharski, "InGaN Laser Diode Mini-Arrays", Appl. Phys. Express 4 (2011) 062103. CrossRef K. Holc, Ł. Marona, R. Czernecki, M. Boćkowski, T. Suski, S. Najda, and P. Perlin, "Temperature dependence of superluminescence in InGaN-based superluminescent light emitting diode structures", J. Appl. Phys. 108 (2010) 013110. CrossRef G. A. Alphonse: "Design of high-power superluminescent diodes with low spectral modulation", Proc. SPIE 4648 (2002) 125. CrossRef P. R. Ashley, M. G. Temmen, and M. Sanghadasa: "Applications of SLDs in fiber optical gyroscopes", Proc. SPIE 4648 (2002) 104. CrossRef J. M. Schmitt: "Optical coherence tomography (OCT): a review", IEEE J. Sel. Top. Quantum Electron. 5 (1999) 1205. CrossRef A. Kafar, S. Stańczyk, S. Grzanka, R. Czernecki, M. Leszczyński, T. Suski, and P. Perlin, "Cavity suppression in nitride based superluminescent diodes", J. Appl. Phys. 111 (2012) 083106. CrossRef A. Kafar, S. Stańczyk, G. Targowski, T. Oto, I. Makarowa, P. Wisniewski, T. Suski, and P. Perlin, "High-Optical-Power InGaN Superluminescent Diodes with "j-shape" Waveguide", Appl. Phys. Express 6 (2013) 092102. CrossRef C. Skierbiszewski, Z.R. Wasilewski, M. Siekacz, A. Feduniewicz, P. Perlin, P. Wisniewski, J. Borysiuk, I. Grzegory, M. Leszczynski, T. Suski and S. Porowski, "Blue-violet InGaN laser diodes grown on bulk GaN substrates by plasma-assisted molecular-beam epitaxy", Applied Physics Letters 86 11114 (2005). CrossRef H. Turski, M. Siekacz, M. Sawicka, G. Cywinski, M. Krysko, S. Grzanka, J. Smalc-Koziorowska, I. Grzegory, S. Porowski, ZR. Wasilewski, C. Skierbiszewski, " High quality m-plane GaN grown under nitrogen-rich conditions by plasma assisted molecular beam epitaxy", J. Vac. Sci. Technol. B29, 03C136 (2011). CrossRef H. Turski, M. Siekacz, M. Sawicka, Z. R. Wasilewski, S. Porowski and C. Skierbiszewski, "Role of Nonequivalent Atomic Step Edges in the Growth of InGaN by Plasma-Assisted Molecular Beam Epitaxy", Japanese Journal of Applied Physics 52 (2013) 08JE02. CrossRef H. Turski, M. Siekacz, Z.R. Wasilewski, M. Sawicka, S. Porowski, and C. Skierbiszewski, "Nonequivalent atomic step edges—Role of gallium and nitrogen atoms in the growth of InGaN layers", J. Cryst. Growth 367, 115 (2013). CrossRef C. Skierbiszewski, M. Siekacz, H. Turski, G. Muziol, M. Sawicka, P. Wolny, G. Cywiński, L. Marona, P. Perlin, P. Wiśniewski, M. Albrecht, Z. R. Wasilewski, S. Porowski, "True-Blue Nitride Laser Diodes Grown by Plasma-Assisted Molecular Beam Epitaxy", Applied Physics Express 5 112103 (2012). CrossRef